Transformational Leadership And Organizational Culture As Predictors Of Teachers’ Organizational Commitment: The Moderating Effect Of Work Engagement - Kuswanto, Kuswanto; Nurdiana, Ratna (Equator Journal of Management and Entrepreneurship (EJME), 2026)
Organizational commitment is a critical factor in enhancing educational effectiveness, particularly amid increasing institutional demands and reforms. This study examines the influence of transformational leadership and organizational culture on teachers’ organizational commitment, as well as the moderating role of work engagement in these relationships. Drawing upon transformational leadership theory, organizational culture theory, and engagement theory, the study proposes an integrative structural model to explain both direct and interaction effects. A quantitative cross-sectional survey was conducted involving 367 teachers who are members of PGRI Kabupaten Lamongan, Indonesia. Data were analyzed using Structural Equation Modeling (SEM) with AMOS to test the measurement and structural models, including moderation effects through interaction terms. The results indicate that transformational leadership and organizational culture both have positive and significant direct effects on teachers’ organizational commitment. Furthermore, work engagement significantly moderates these relationships, strengthening the influence of leadership and organizational culture on commitment when teachers demonstrate high levels of vigor, dedication, and absorption. The structural model shows excellent goodness-of-fit indices, confirming its statistical robustness and theoretical adequacy. These findings highlight the strategic importance of fostering transformational leadership practices, cultivating a supportive organizational culture, and enhancing teachers’ work engagement to strengthen organizational commitment. The study contributes to the literature by positioning work engagement not only as an outcome or mediator but also as a boundary condition that amplifies the effects of leadership and culture on teachers’ commitment.